The Effectiveness of the Token Economy to Reduce Student Academic Procrastination - Hera Wahyuni; Nelyahardi Gutji; Affan Yusra; Meri Haryani (Program Studi Bimbingan dan Konseling FKIP UMSU, 2022)
This research is based on the problem of student academic procrastination in online learning during the current covid-19 pandemic. This study aims to describe the results of empirical tests regarding the effectiveness of the token economy strategy to reduce students' academic procrastination. A total of 15 students of class IX at SMPN 8 were used as samples in this study. The instrument used is the PAS Scale. Data analysis includes descriptive analysis, analysis requirements test with normality and homogeneity tests, and hypothesis testing with T-test. The results of the study were the level of student academic procrastination before being given treatment was 53.3%, and after being given treatment decreased by 40%. The T-test obtained a T arithmetic value of 4,567 with sig(2-tailed) 0.000 0.05. the conclusion is the token economy strategy is effective to reduce student academic procrastination.